Ternary transition group intermetallic electron compound and application thereof
Preparation of A4BC type intermetallic electronic compounds between ternary transition group through first-principle calculation and arc smelting, solving the capacity and stability of battery negative electrode materials, and achieving high energy density and cycle stability of battery negative electrode materials, suitable for a variety of Battery Type.
Patent Information
- Application Number
- CN202411246870.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The theoretical specific capacity of existing battery negative electrode materials such as graphite is limited. Silicon-based materials are prone to volume expansion during charging and discharging, resulting in actual capacity decay. The transition group intermetallic electronic compounds lack stability in battery applications, which limits their Widely used in the field of new energy.
The thermodynamically stable and metastable A4BC type ternary transition group intermetallic electronic compounds were obtained through first-principles calculations. The powder or block material with high-energy gap electrons was prepared by arc smelting and annealing treatment, and used for battery negative electrode materials. , enhance the absorption and storage capacity of metal ions.
Achieve a battery negative electrode material with high energy density and good cycle stability, simplifies the preparation process, improves the purity and crystallinity of the material, and is suitable for lithium batteries, sodium batteries, etc., significantly improves the reversible specific capacity and cycle stability of the battery. .
Smart Images

Figure CN119120986A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ternary intermetallic electronic compound materials, and in particular relates to a ternary transition metal intermetallic electronic compound and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, wearable devices and other fields, the performance and demand for batteries are growing rapidly. Among them, the negative electrode material, as one of the four key materials of the battery, has a great influence on the battery's energy density, cycle performance, charge and discharge rate and other performance.
[0003] Currently, graphite is the most widely used battery negative electrode material. However, its theoretical specific capacity is limited to 372 mAhg -1 , which limits the further improvement of battery performance. To this end, researchers continue to explore new negative electrode materials, such as lithium titanate, silicon-based and tin-based materials, in order to break through this limitation. Among them, silicon-based materials are eye-catching for their ultra-high theoretical capacity, but unfortunately, they are prone to volume expansion during the charging and discharging process, resulting in a significant attenuation of the actual capacity, thus limiting their wide application.
[0004] Electronic compounds are a special class of compounds in which electrons act as anions. Among them, anionic electrons are periodically localized in the interstitial space and occupy high energy bands (crossing or close to the Fermi level), which makes the electrons easily excited and has a wide range of applications in a series of catalytic fields such as synthetic ammonia, CO reduction and selective catalytic hydrogenation. However, due to the active electrons, most electronic compounds are unstable and easily oxidized and decomposed in air and water. Their battery applications mostly remain in the theoretical exploration stage, including transition metal intermetallic electronic compounds, and there are few application cases of actual battery testing. Therefore, the study of stable transition metal intermetallic electronic compounds as battery negative electrode materials is not only expected to solve the current capacity and stability problems of negative electrode materials, but also to open up new paths for the application of electronic compounds in the field of energy storage. This exploration is not only of far-reaching significance for the research of electronic compounds themselves, but will also provide strong support for the continuous advancement of battery technology. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a ternary transition metal intermetallic compound and its application. Specifically, due to the hybridization between interstitial electrons and metal atoms, the intermetallic compound has high stability. Therefore, based on the first principles, we calculated the energy and electronic structure of a series of ternary intermetallic compounds composed of non-precious metals (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo and Hf and other elements) in the transition group, and obtained a total of seven A4BC-type ternary transition metal intermetallic compounds that are theoretically thermodynamically stable and metastable, which were then successfully synthesized and applied to battery performance testing. The ternary transition metal intermetallic compound has The electronic compound of the present invention has the characteristics of spatial structure, and the structural gap has high-energy interstitial electrons, which can migrate between the adsorbed metal layers to stabilize the positively charged metal ion layers together. At the same time, the high-energy interstitial position of the electrons is also conducive to the embedding of metal ions, thereby enhancing the absorption of metal ions and increasing the storage capacity.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The first object of the present invention is to provide a ternary transition metal intermetallic compound, wherein the molecular formula of the transition metal intermetallic compound is A4BC; wherein the transition metal A is Ti, Zr or Hf; the transition metal B is Mn, Fe, Co or Ni; and the transition metal C is Fe, Co, Ni or Mo; and the transition metal intermetallic compound has Type crystal structure.
[0008] Furthermore, the molecular formula of the transition metal intermetallic compound is Ti4MnNi, Zr4FeMo, Zr4CoMo, Zr4NiMo, Hf4MnFe, Hf4MnCo or Hf4FeCo.
[0009] Furthermore, the transition metal intermetallic compound is in the form of any one of powder, bulk, and thin film, or a combination of two or more thereof.
[0010] Furthermore, when the transition metal intermetallic compound is in the form of powder, the particle size is 1 μm to 100 μm.
[0011] The second object of the present invention is to provide a method for preparing the above-mentioned ternary transition metal intermetallic compound, comprising the following steps:
[0012] According to the stoichiometric ratio, transition metal A powder, B powder and C powder are weighed, mixed evenly, pressed into a shape at 2MPa to 10MPa, and smelted to obtain alloy A4BC;
[0013] In an inert gas atmosphere, the alloy A4BC is annealed at 200°C to 1800°C to obtain a transition metal intermetallic compound.
[0014] Furthermore, the annealing treatment time is 1 h to 300 h, the inert gas is argon, and the heating rate is 1° C. / min to 5° C. / min.
[0015] Furthermore, the smelting method adopts arc melting.
[0016] Furthermore, the particle sizes of the transition metal A powder, B powder and C powder are 50 mesh to 500 mesh.
[0017] The third object of the present invention is to provide the use of the above-mentioned ternary transition metal intermetallic compound in the preparation of battery negative electrode materials.
[0018] Furthermore, the battery is a lithium battery, a sodium battery or a potassium battery.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention provides an A4BC type ternary transition metal intermetallic compound having The electronic compound of the present invention has the characteristics of spatial structure, and the structural gap has high-energy interstitial electrons, which can migrate between the adsorbed metal layers to stabilize the positively charged metal ion layers together. At the same time, the high-energy interstitial position of the electrons is also conducive to the embedding of metal ions, thereby enhancing the absorption of metal ions and increasing the storage capacity.
[0021] (2) The preparation method of the A4BC-type ternary transition metal intermetallic electronic compound of the present invention is simple, the preparation cycle is short and it is easy to synthesize. The purity and crystallinity of the obtained material are better, the room temperature stability is good, and it is conducive to battery performance testing. The A4BC-type ternary transition metal intermetallic electronic compound can be used as a negative electrode material for batteries. The prepared battery has a high reversible specific capacity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the thermodynamic ternary phase diagram of the Ti4MnNi ternary transition metal intermetallic electronic compound according to Example 1 of the present invention.
[0023] Figure 2 This is the thermodynamic ternary phase diagram of the Zr4FeMo ternary transition metal intermetallic electronic compound according to Example 2 of the present invention.
[0024] Figure 3 This is the thermodynamic ternary phase diagram of the ternary transition metal intermetallic compound Zr4CoMo according to Example 3 of the present invention.
[0025] Figure 4This is the thermodynamic ternary phase diagram of the ternary transition metal intermetallic compound Zr4NiMo according to Example 4 of the present invention.
[0026] Figure 5 This is the thermodynamic ternary phase diagram of the ternary transition metal intermetallic compound Hf4MnFe according to Example 5 of the present invention.
[0027] Figure 6 This is the thermodynamic ternary phase diagram of the Hf4MnCo ternary transition metal intermetallic electronic compound according to Example 6 of the present invention.
[0028] Figure 7 This is the thermodynamic ternary phase diagram of the Hf4FeCo ternary transition metal intermetallic electronic compound according to Example 7 of the present invention.
[0029] Figure 8 This is the electronic structure diagram of the Ti4MnNi ternary transition metal intermetallic compound of Example 1 of the present invention, wherein: Figure 8 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0030] Fig. 9 The electronic structure diagram of the Zr4FeMo ternary transition metal intermetallic compound of Example 2 of the present invention, wherein: Fig. 9 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0031] Fig.10 The electronic structure diagram of the ternary transition metal intermetallic compound 3Zr4CoMo of the present invention, wherein: Fig.10 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0032] Fig.11 The electronic structure diagram of the ternary transition metal intermetallic compound 4Zr4NiMo of the present invention, wherein: Fig.11 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0033] Fig.12 This is the electronic structure diagram of the ternary transition metal intermetallic compound 5Hf4MnFe of the present invention, wherein: Fig.12 Figure (a) is the local charge function, and (b) is the anion electron projected energy band.
[0034] Fig.13 The electronic structure diagram of the ternary transition metal intermetallic compound Hf4MnCo of Example 6 of the present invention, wherein: Fig.13 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0035] Fig.14 The electronic structure diagram of the ternary transition metal intermetallic compound Hf4FeCo of the embodiment of the present invention is shown in FIG. Fig.14 (a) is the local charge function, and (b) is the anion electron projected energy band.
[0036] Fig.15 This is the XRD diagram of the Ti4MnNi ternary transition metal intermetallic compound according to Example 1 of the present invention.
[0037] Fig.16 This is the XRD diagram of the ternary transition metal intermetallic compound Zr4FeMo according to Example 2 of the present invention.
[0038] Fig.17 This is the XRD diagram of the ternary transition metal intermetallic compound 3Zr4CoMo according to Example 3 of the present invention.
[0039] Fig.18 This is the XRD diagram of the ternary transition metal intermetallic compound 4Zr4NiMo according to Example 4 of the present invention.
[0040] Fig.19 This is the XRD diagram of the ternary transition metal intermetallic compound 5Hf4MnFe according to Example 5 of the present invention.
[0041] Fig. 20 This is the XRD diagram of the Hf4MnCo ternary transition metal intermetallic compound according to Example 6 of the present invention.
[0042] Fig.21 This is the XRD diagram of the Hf4FeCo ternary transition metal intermetallic compound according to Example 7 of the present invention.
[0043] Fig. 22 This is a performance test diagram of the ternary transition metal intermetallic electronic compound used as a negative electrode material for a lithium battery in Examples 1 and 7 of the present invention, wherein: Fig. 22 (a) is Ti4MnNi, and (b) is Hf4FeCo.
[0044] Fig.23 This is a performance test diagram of the compounds in Example 1 and Comparative Example 1 of the present invention for use as negative electrode materials for sodium ion batteries, wherein: Fig.23 Among them, (a) is Ti4MnNi, and (b) is Ca2N. DETAILED DESCRIPTION
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0047] In one aspect, the present invention provides a ternary transition metal intermetallic compound, wherein the molecular formula of the transition metal intermetallic compound is A4BC; wherein the transition metal A is Ti, Zr or Hf; the transition metal B is Mn, Fe, Co or Ni; the transition metal C is Fe, Co, Ni or Mo; the transition metal
[0048] —Intergeneric electron compounds have F43m type crystal structure.
[0049] The present invention provides a ternary transition metal intermetallic compound, which is prepared by using transition metal elements A, B, and C to prepare an electronic compound with an A4BC type molecular formula, wherein the interstitial electrons of the electronic compound with the A4BC type molecular formula are localized in the octahedral gap of the A element, and the smaller electronegativity (such as Ti, Zr and Hf) helps the electrons to be localized in the gap instead of being attracted by atoms around the atomic nucleus, so that it is easy to form an electronic compound.
[0050] The obtained electronic compound has the characteristics of F43m spatial structure. There are multiple high-energy interstitial electron sites in the unit cell of this structure, while there are only one or two interstitial electron sites in the structure of most other electronic compounds. These electrons can migrate between the adsorbed metal layers to stabilize the positively charged metal ion layers together. At the same time, this high-energy interstitial position of the electrons is also conducive to the embedding of metal ions, thereby enhancing the absorption of metal ions and increasing the storage capacity.
[0051] In a specific embodiment, the molecular formula of the transition metal intermetallic compound is Ti4MnNi, Zr4FeMo, Zr4CoMo, Zr4NiMo, Hf4MnFe, Hf4MnCo or Hf4FeCo. The electronic structure of the transition metal intermetallic compound is characterized by the presence of interstitial localized electrons with high energy levels in the interstitial space surrounded by the transition metal, and the charge localization feature can be determined by first principle calculations.
[0052] Depend on Figures 1 to 7 It can be seen that Zr4FeMo, Zr4CoMo, Hf4MnFe, Hf4MnCo and Hf4FeCo obtained by first-principles calculations are all thermodynamically stable, indicating that these compounds can be synthesized experimentally in theory. hull The values are greater than 0, 0.012eV / atom and 0.01eV / atom respectively, which are metastable structures, but they still have the potential for experimental synthesis. Figures 8 to 14 It can be seen that the results obtained from the first-principles calculations show that Ti4MnNi, Zr4FeMo, Zr4CoMo, Zr4NiMo, Hf4MnFe, Hf4MnCo and Hf4FeCo all have significant characteristics of electronic compounds. The charge localization function diagram (Isosurfaces = 0.7) shows that there are multiple electron localizations in the crystal structure, and different localization sites are represented by V1, V2, and V3, and the projected energy band of the localized electrons is located near the Fermi level.
[0053] In a specific embodiment, the transition metal intermetallic compound is in the form of any one of powder, block, and thin film, or a combination of two or more thereof. When the transition metal intermetallic compound is in the form of powder, the particle size is 1 μm to 100 μm.
[0054] On the other hand, the present invention provides a method for preparing the above-mentioned ternary transition metal intermetallic compound, comprising the following steps:
[0055] S1. According to the stoichiometric ratio, the transition metal A powder, B powder and C powder are weighed, mixed evenly, and then pressed and formed at 2MPa to 10MPa, and the alloy A4BC is obtained by smelting; it should be noted that the present invention does not limit the specific process of smelting A, B and C into the alloy A4BC, as long as the three elements A, B and C can be fully mixed and evenly formed to form an A4BC alloy with uniform components. The present invention preferably adopts arc melting method for smelting, and its specific process is as follows: the weighed and evenly mixed metal powder is pressed into small pieces by a tablet press at 2MPa to 10MPa, placed in a copper crucible of a smelting furnace, and then arc melted in an argon atmosphere. During arc melting, the current is adjusted to make the sample in a molten state, and maintained for 3 seconds to 15 seconds; the metal ingot is turned over and smelted repeatedly for 1 to 10 times. Among them, the present invention does not limit the specific size of the current, and can be adjusted according to the actual selected materials of A, B, and C, as long as the sample can be in a molten state.
[0056] S2. The arc-melted A4BC alloy is crushed in a glove box, and then the alloy powder is wrapped with tantalum foil and packaged in a quartz tube. In an inert gas atmosphere, the alloy A4BC is annealed at 200°C to 1800°C to obtain a transition metal intermetallic compound. It should be noted that the present invention does not limit the specific annealing temperature and annealing time, and can be adjusted according to the actual selected materials of A, B, and C to achieve the purpose of forming a compound of the three elements and making the sample uniform and having a good purity. Optionally, the present invention is annealed at 200°C to 1800°C for 1h to 300h, and the heating rate is 1°C / min to 5°C / min. Preferably, the annealing temperature is 700°C to 1400°C, and the annealing time is 200h to 300h.
[0057] In a specific embodiment, the particle size of the transition metal A powder, B powder and C powder is 50 mesh to 500 mesh.
[0058] The third object of the present invention is to provide the use of the above-mentioned A4BC type ternary transition metal intermetallic electronic compound in the preparation of battery negative electrode materials. The battery is a lithium battery, a sodium battery or a potassium battery. The A4BC type ternary transition metal intermetallic electronic compound is stable at room temperature, which is conducive to battery performance testing. When it can be used for battery negative electrode materials, the prepared battery has high reversible specific capacity and good cycle stability.
[0059] The invention is further described below through specific examples.
[0060] Example 1
[0061] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Ti4MnNi.
[0062] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0063] S1. Weigh Ti, Mn and Ni metal powders according to the stoichiometric ratio of Ti: Mn: Ni = 4: 1: 1 and mix them. The particle size of the metal powders of Ti, Mn and Ni is 100 mesh. Then, use a tablet press to press the mixed metal powders into small pieces at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10 -5Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Ti4MnNi;
[0064] S2. Grind the cooled Ti4MnNi alloy sample in a mortar to obtain a powder sample of the Ti4MnNi alloy; wrap the obtained Ti4MnNi alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box; heat the quartz tube to 900°C at a heating rate of 3°C / min and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Ti4MnNi electronic compound.
[0065] Example 2
[0066] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Zr4FeMo.
[0067] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0068] S1. Weigh and mix metal powders of Zr, Fe and Mo according to the stoichiometric ratio of Zr:Fe:Mo=4:1:1. The particle size of the metal powders of Zr, Fe and Mo is 100 mesh. Then, press the mixed metal powders into small pieces with a tablet press at 2MPa-10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10 -5 Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Zr4FeMo;
[0069] S2. Grind the cooled Zr4FeMo alloy sample in a mortar to obtain a powder sample of the Zr4FeMo alloy; wrap the obtained Zr4FeMo alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box; heat the quartz tube to 1000°C at a heating rate of 3°C / min, and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Zr4FeMo electronic compound.
[0070] Example 3
[0071] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Zr4CoMo.
[0072] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0073] S1. Weigh and mix metal powders of Zr, Co and Mo according to the stoichiometric ratio of Zr: Co: Mo = 4: 1: 1. The particle size of the metal powders of Zr, Co and Mo is 100 mesh. Then, press the mixed metal powders into small pieces with a tablet press at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and evacuate the chamber with a molecular pump to a vacuum value of 10 -5 Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Zr4CoMo;
[0074] S2. Grind the cooled Zr4CoMo alloy sample in a mortar to obtain a powder sample of the Zr4CoMo alloy; wrap the obtained Zr4CoMo alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box. Heat the quartz tube to 1000°C at a heating rate of 3°C / min and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Zr4CoMo electronic compound.
[0075] Example 4
[0076] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Zr4NiMo.
[0077] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0078] S1. Weigh Zr, Ni, and Mo metal powders according to the stoichiometric ratio of Zr:Ni:Mo=4:1:1 and mix them. The particle size of the metal powders of Zr, Ni, and Mo is 100 mesh. Then, use a tablet press to press the mixed metal powders into small pieces at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10. -5Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Zr4NiMo;
[0079] S2. Grind the cooled Zr4NiMo alloy sample in a mortar to obtain a powder sample of the Zr4NiMo alloy; wrap the obtained Zr4NiMo alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box. Keep the quartz tube at 1000°C for 160h, and finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Zr4NiMo electronic compound.
[0080] Example 5
[0081] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Hf4MnFe.
[0082] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0083] S1. Weigh Hf, Mn, and Fe metal powders according to the stoichiometric ratio of Hf: Mn: Fe = 4: 1: 1 and mix them. The particle size of the metal powders of Hf, Mn, and Fe is 100 mesh. Then, use a tablet press to press the mixed metal powders into small pieces at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10. -5 Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Hf4MnFe;
[0084] S2. Grind the cooled Hf4MnFe alloy sample in a mortar to obtain a powder sample of the Hf4MnFe alloy; wrap the obtained Hf4MnFe alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box; heat the quartz tube to 1000°C at a heating rate of 3°C / min, and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Hf4MnFe electronic compound.
[0085] Example 6
[0086] The invention discloses an A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Hf4MnCo.
[0087] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0088] S1. Weigh Ti, Mn and Ni metal powders according to the stoichiometric ratio of Hf: Mn: Co = 4: 1: 1 and mix them. The particle size of the metal powders of Ti, Mn and Ni is 100 mesh. Then, use a tablet press to press the mixed metal powders into small pieces at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10 -5 Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Hf4MnCo;
[0089] S2. Grind the cooled Hf4MnCo alloy sample in a mortar to obtain a powder sample of the Hf4MnCo alloy; wrap the obtained Hf4MnCo alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box; heat the quartz tube to 1000°C at a heating rate of 3°C / min and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Hf4MnCo electronic compound.
[0090] Example 7
[0091] An A4BC type ternary transition metal intermetallic compound material, whose molecular formula is Hf4FeCo.
[0092] The preparation method of the above-mentioned A4BC type ternary transition metal intermetallic compound material comprises the following steps:
[0093] S1. Weigh Hf, Fe, and Co metal powders according to the stoichiometric ratio of Hf:Fe:Co=4:1:1 and mix them. The particle size of the metal powders of Hf, Fe, and Co is 100 mesh. Then, use a tablet press to press the mixed metal powders into small pieces at 2MPa to 10MPa and put them into a micro metal melting furnace. Before melting, flush the melting furnace cavity with argon gas and use a molecular pump to evacuate the chamber to a vacuum value of 10. -5Pa, repeated 3 times, after the last filling of Ar gas at -0.2MPa, deoxidation was carried out using Ti particles; then, the pressed metal pieces were placed in a copper crucible of a melting furnace and arc-melted in an argon atmosphere, and the current was adjusted during arc melting so that the sample was in a molten state and maintained for 7 seconds, then turned over and continued to melt so that the molten state was maintained for 7 seconds, and the melting was repeated 6 times to ensure uniform melting of the alloy, and the sample was taken out after cooling to obtain the alloy Hf4FeCo;
[0094] S2. Grind the cooled Hf4FeCo alloy sample in a mortar to obtain a powder sample of the Hf4FeCo alloy; wrap the obtained Hf4FeCo alloy powder with tantalum foil and package it in a quartz tube under an argon atmosphere in a glove box; heat the quartz tube to 900°C at a heating rate of 3°C / min and keep it warm for 160h. Finally, take out the sample from the quartz tube in the glove box and grind it to obtain the final Hf4FeCo electronic compound.
[0095] Comparative Example 1
[0096] Electron compound Ca2N.
[0097] The structures of the ternary transition metal intermetallic compounds prepared in Examples 1-7 were tested, and the results are as follows.
[0098] Fig.15 This is the XRD diagram of the Ti4MnNi ternary transition metal intermetallic compound of Example 1 of the present invention; Fig.16 The XRD diagram of the ternary transition metal intermetallic compound Zr4FeMo of Example 2 of the present invention; Fig.17 The XRD diagram of the ternary transition metal intermetallic compound 3Zr4CoMo of the embodiment of the present invention; Fig.18 The XRD diagram of 4Zr4NiMo, a ternary transition metal intermetallic compound, according to the embodiment of the present invention; Fig.19 The XRD diagram of the ternary transition metal intermetallic compound 5Hf4MnFe of the embodiment of the present invention; Fig. 20 The XRD diagram of the ternary transition metal intermetallic compound Hf4MnCo of Example 6 of the present invention; Fig.21 The XRD diagram of the ternary transition metal intermetallic compound Hf4FeCo of Example 7 of the present invention is shown in FIG. Figure 15-21 It can be seen that the samples of the A4BC-type ternary transition metal intermetallic compound materials prepared in Examples 1-7 of the present invention have very good purity and very good crystallinity.
[0099] The ternary transition metal intermetallic electronic compounds prepared in Example 1 and Example 7 were used as negative electrode materials for lithium batteries to conduct battery performance tests. The test method was as follows: first, 70 wt% of active material, 20 wt% of carbon black and 10 wt% of polyvinylidene fluoride (PVDF) were uniformly ground in 1-methyl-2-pyridone (NMP), and then the resulting slurry was coated on a copper foil. After vacuum drying at 60°C for 24 hours, a circular electrode with a diameter of 12 mm was obtained using a slicer. Coin cells were then assembled in an argon-filled glove box. The counter electrode, electrolyte and diaphragm used were lithium foil, 1M lithium hexafluorophosphate (LiPF6) and polypropylene microporous membrane, respectively. The assembled coin cells were tested using a Neware battery testing system in Shenzhen, China. The test results are shown in the figure. Fig. 22 shown.
[0100] Fig. 22 This is a performance test diagram of the A4BC type ternary transition metal intermetallic electronic compound used as a negative electrode material for a lithium battery in Examples 1 and 7 of the present invention, wherein: Fig. 22 (a) is Ti4MnNi, (b) is Hf4FeCo. Fig. 22 It can be seen that both Ti4MnNi and Hf4FeCo negative electrode materials have high charge and discharge specific capacity and good cycle stability. -1 At a current density of 1.34 W, the reversible specific capacity of Ti4MnNi is stable at 181 mAh g at 500 cycles. -1 The reversible specific capacity of Hf4FeCo is stable at 282 mAh g at 280 cycles. -1 This indicates that the A4BC type ternary transition metal intermetallic compound material prepared by the present invention can be used as a negative electrode material for lithium batteries.
[0101] The ternary transition metal intermetallic electronic compound prepared in Example 1 was used as the negative electrode material of the sodium battery to carry out the battery performance test. The test method was as follows: first, 70 wt% of the active material, 20 wt% of the carbon black and 10 wt% of the polyvinylidene fluoride (PVDF) were uniformly ground in 1-methyl-2-pyridone (NMP), and then the obtained slurry was coated on the copper foil. After vacuum drying at 60°C for 24 hours, a circular electrode with a diameter of 12 mm was obtained using a slicer. Then, the coin battery was assembled in a glove box filled with argon gas. The counter electrode, electrolyte and diaphragm used were sodium foil, 1M sodium perchlorate (NaClO4) and glass fiber membrane, respectively. The assembled coin battery was tested using the Neware battery test system in Shenzhen, China.
[0102] Comparative Example 1 Sodium ion battery test method for electronic compound Ca2N (refer to ACSAppl.Mater.Interfaces, 2017, 9, 8, 6666-6669): First, wash the nickel foam (100mm×50mm×1mm) three times with deionized water and ethanol respectively, and then dry it in a vacuum oven at 80°C overnight. Then, scratch one side (side A) of the nickel foam to reduce the pore size of the surface. Next, a slurry mixed with Super P (Timcal) and polyvinylidene fluoride (PVDF) adhesive in a weight ratio of 2:1 is coated on the a surface and dried in a vacuum oven at 80°C overnight. Since the pores on the A surface are blocked, the Ca2N powder cannot pass through the nickel foam. A thin sheet with a diameter of 11 mm is punched from the coated nickel foam and used as a current collector, with a dry composite mass loading of 5.5 mg·cm -2 Then, the Ca2N powder was dispersed on the other side (side B) of the current collector that was not coated with the composite slurry (Super P and PVDF). After calendering at 8 MPa for 2 min, a Ca2N with a mass loading of about 1.7 mg cm -2 Compression-molded electrodes for sodium battery performance testing.
[0103] Fig.23 This is a performance test diagram of the compounds in Example 1 and Comparative Example 1 of the present invention for use as negative electrode materials for sodium ion batteries, wherein: Fig.23 (a) is Ti4MnNi, (b) is Ca2N. Fig.23 It can be seen that: Example 1 Ti4MnNi has good stability when used as a negative electrode material for sodium ion batteries. -1 At a current density of 1.34 W, the reversible specific capacity of Ti4MnNi is stable at 80 mAh g within 330 cycles. -1 The Ca2N is around 0.05A·g -1 At a current density of 300 mAh g -1 The reversible specific capacity of the battery was only maintained for 35 cycles, and the reversible specific capacity dropped to 180 mAh g at 50 cycles. -1 This indicates that the A4BC type ternary transition metal intermetallic compound material prepared by the present invention can be used as a stable negative electrode material for sodium batteries.
[0104] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0105] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A ternary transition metal intermetallic compound, characterized in that: The molecular formula of the transition metal intermetallic compound is A4BC; wherein the transition metal A is Ti, Zr or Hf; the transition metal B is Mn, Fe, Co or Ni; the transition metal C is Fe, Co, Ni or Mo; the transition metal intermetallic compound is The electronic compound has a F43m-type crystal structure.
2. The ternary transition metal intermetallic compound according to claim 1, characterized in that: The molecular formula of the transition metal intermetallic compound is Ti4MnNi, Zr4FeMo, Zr4CoMo, Zr4NiMo, Hf4MnFe, Hf4MnCo or Hf4FeCo.
3. The ternary transition metal intermetallic compound according to claim 1, characterized in that: The transition metal intermetallic compound is in the form of any one of powder, block, and thin film, or a combination of two or more thereof.
4. The ternary transition metal intermetallic compound according to claim 1, characterized in that: When the transition metal intermetallic compound is in the form of powder, the particle size is 1 μm to 100 μm.
5. A method for preparing a ternary transition metal intermetallic compound according to any one of claims 1 to 4, characterized in that: The following steps are involved: Weigh transition metal A powder, B powder and C powder according to the stoichiometric ratio, mix them evenly, press them into a shape, and then smelt them to obtain alloy A4BC; In an inert gas atmosphere, the alloy A4BC is annealed at 200°C to 1800°C to obtain a transition metal intermetallic compound.
6. The method for preparing a ternary transition metal intermetallic compound according to claim 5, characterized in that: The annealing treatment time is 1h to 300h, the inert gas is argon, and the heating rate is 1°C / min to 5°C / min.
7. The method for preparing a ternary transition metal intermetallic compound according to claim 5, characterized in that: The smelting method adopts arc smelting.
8. The method for preparing a ternary transition metal intermetallic compound according to claim 5, characterized in that: The particle sizes of the transition metal A powder, B powder and C powder are 50 meshes to 500 meshes.
9. Use of the ternary transition metal intermetallic compound according to any one of claims 1 to 4 in the preparation of battery negative electrode materials.
10. The use according to claim 9, characterized in that: The battery is a lithium battery, a sodium battery or a potassium battery.
Citation Information
Patent Citations
Semi-liquid metal power lithium battery suitable for deep sea pressure withstanding
CN108470902A
TiS2 composite positive electrode and all-solid-state battery device
CN116666566A
AB3 type binary intermetallic electron compound material as well as preparation method and application thereof
CN116790921A
Methods of reducing the bandgap energy of a metal oxide
US20070235711A1
Negative electrode active material, negative electrode, and battery
US20190190021A1
